An evaluation of the microbiota of the upper reproductive tract of women with and without epithelial ovarian cancer - Wendy R. Brewster; Wesley C. Burkett; Emily M. Ko; Victoria Bae-Jump; Amber Nicole McCoy; Temitope O. Keku (Elsevier, 2022)
Objective: The microbiome of the female upper reproductive tract (URT) has not been characterized. We hypothesize that distinct bacterial species may be identified in different areas of the URT in women with or without ovarian cancers. Methods: Postmenopausal women scheduled for salpingooophorectomy were prospectively identified. We excluded those who used antibiotics within three months of surgery or had a diagnosed gynecologic cancer. Bacteria were extracted from tissue samples of the proximal fallopian tube, fimbriae and ovaries of 10 women. Using molecular-phylogenetic methods based on the highly conserved 16S bacteria rRNA gene, we assessed the complexity of URT microbiota in tissue samples by high throughput sequencing of the V1-V3 region of the 16S gene. Sequences were processed through QIIME and an average of 69,625 reads per sample was obtained after quality filtering. Multivariate analyses were conducted using PRIMER VI software. Results: The initial analysis of samples suggests that bacteria exist in the URT. Analysis of similarity matrix (ANOSIM) suggests that the microbiome differs in the areas examined (ANOSIM R = 0.26, p = 0.015). The microbiome differs significantly between the fallopian tube and ovary (ANOSIM R = 0.23, p = 0.02). The proximal fallopian tube microbiome also differs from the fimbriae (ANOSIM R = 0.66, p = 0.025). There were borderline differences in the microbial profiles of the specimens with and without epithelial ovarian cancer (p = 0.06). Conclusions: We identified distinct microbiota of the ovaries and fallopian tubes with a profile unique to women with epithelial ovarian cancer. Further investigation is necessary to determine whether the microbiome is related to ovarian carcinogenesis.